Coalescing microstructure and fabric transitions with AMS data in deformed limestone: Implications on deformation kinematics. (September 2018) - Ghosh, Bhaskar; Das, Paramita; Sarkar, Dyuti Prakash; Ghosh, Gautam; Mukhopadhyay, Joydip; Ando, Jun-ichi
Abstract: The microstructures of the heterogeneously deformed limestones of the Kolhan Group, Singhbhum Craton (SC), eastern India are investigated to study deformation mechanism, grain size and shape preferred orientation (SPO) development. The texture of the deformed rocks is analyzed by Electron Back-Scattered Diffraction (EBSD) in order to determine crystallographic preferred orientation (CPO) development in calcite grains. The c-axis pattern in protomylonite and mylonite define girdle patterns developed perpendicular to local shear planes showing monoclinic symmetry. The latter is interpreted in terms of a top-to-south shear, which is consistent with the observed microstructural and fabric data from the deformed rocks. The Anisotropy of Magnetic Susceptibility (AMS) studies are performed on 22 heterogeneously strained limestone specimens to document strain variation within the Kolhan rocks. The field fabric, SPO data measured from calcite and mica grains (κcal and κmi ) and calcite CPO data are compared with observed variation in AMS fabric intensity (Pj) across the Kolhan basin. Integration of these data sets help to establish presence of large internal thrust planes within the Kolhan basin, which form a part of the regional foreland vergent thrust system developed along the northern margin of the SC. Highlights: The deformed limestones of the Kolhan basin show evidences of heterogeneous deformation. The variation in SPO intensity (κ) is determined, separately from calcite and mica fraction, across the rocks of the belt. CPO pattern and fabric strength (TLPO, PLPO ) is measured from calcite grains in selected samples. AMS analysis is done from deformed limestones to record strain heterogeneity within the belt. Integration of SPO, CPO and AMS data with field observations help deciphering large-scale kinematics of deformation.